Tourism and transition : governance, transformation and development (CABI, 2004)
This book presents current research on the roles and importance of tourism and its interrelationships with governance and development in transition economies and those adjusting to the accession requirements of the enlarged EU. The geographical coverage ranges across Central and Eastern Europe, the Central and Eastern Mediterranean, Central Asia, China and South Africa. Throughout this volume, the interaction of cultural, economic and political factors in the processes of tourism development is emphasized. The book has 15 chapters and a subject index.